AN ANALYSIS OF EDUCATIONAL VALUES IN THE NUN FILM - Agnes Larasati; Ana Shofiana Jamilah; Marginingsih Marginingsih (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2021)
The purpose of this study is to find out what education values are in the Nun film. The author explain the discussion of educational values in literary works. This form of education can be observed from the psychological side and daily actions. This can also be developed in literary works as teaching to understand and find positive values analyzed by the author. This study findsd that the educational values taken from analyzing of several roles and dialogues in the film such as courage, religion, self- confidence, responsibility, sacrifice, determination, helpfull, and emotional control.